A steep-switching impact ionization-based threshold switching field-effect transistor. Issue 12 (1st March 2023) - Kang, Chanwoo; Choi, Haeju; Son, Hyeonje; Kang, Taeho; Lee, Sang-Min; Lee, Sungjoo
Abstract : A steep switching transistor (subthreshold swing, SS ∼32.8 mV dec −1 ) with low dielectric injection efficiency (Δ I GS /Δ I DS ∼10 −6 is constructed by connecting an MoS2 FET and a WSe2 impact-ionisation based threshold switch. Abstract : A steep switching device with a low subthreshold swing (SS) that overcomes the fundamental Boltzmann limit ( kT / q ) is required to efficiently process a continuously increasing amount of data. Recently, two-dimensional material-based impact ionization transistors with various structures have been reported with the advantages of a low critical electric field and a unique quantum confinement effect. However, most of them cannot retain steep switching at room temperature, and device performance degradation issues caused by impact ionization-induced hot carriers have not been structurally addressed. In this study, we presented an impact-ionization-based threshold switching field-effect transistor (I 2 S-FET) fabricated with a serial connection of a MoS2 FET and WSe2 impact ionization-based threshold switch (I 2 S). We obtained repetitive operation with low SS (32.8 mV dec −1 ) at room temperature, along with low dielectric injection efficiency (10 −6 ), through a structural design with separation of the conducting region, which determines on-state carrier transport, and the steep-switching region where the transition from off- to on-state occurs via impact ionization. Furthermore, compared to previously reported threshold-switching devices, our device demonstrated hysteresis-free switching characteristics. This study provides a promising approach for developing next-generation energy-efficient electronic devices and ultralow-power applications.